(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
Servo motors have been adopted in various industry applications, as a result of which there has been a trend toward improving their speed accuracy. DC servomotors with feedback encoders established themselves as participants for various motion control applications in industrial automation and consumer electronics. This article presents speed control of DC servomotors with different control methods (traditional PID, fuzzy logic, and hybrid PID–fuzzy logic controller). Although of simplicity, there are constraints to the PID controllers for nonlinearities and uncertainties; hence, a significant step has been made toward intelligent and hybrid control strategies. In MATLAB Simulink the control performance of these controllers is simulated, and it is noted that the hybrid PID–fuzzy logic controller has less settling time, very little overshoot, and near-zero steady-state error. This hybrid approach offers the accuracy of the PID control system and the flexibility of the fuzzy logic controller and introduces a robust and effective method to enhance the motor speed response for the servo motor application. applications,